(untitled) (Jurnal Pelita Pendidikan, 2016)
This research aims to determine the effect of 5E (Engagement - Exploration “ Explanation “ Elaboration “ Evaluation) Learning Model toward student learning outcomes on human nervous system concepts. This research was conducted in SMA Negeri 8 Medan, academic year 2014/2015. The method used in this study is quasi-experimental methods. The population in this research is all grade XI science students SMAN 8 Medan with 5 (five) classes academic year 2014/2015. From the population was taken 80 students as the sample by using random sampling. They are students of class XI Science 3 (consist of 40 students) as an experimental class use 5E Learning Model, while the students of class XI IPA 4 (consist of 40 students) as a control use direct learning model. The early data be obtained from the average pretest that value of 55.16 post-test from experimental class and control class 53.66. For posttest in experiment class is 80.92 and control class is 74.33. After that tested by normality test, homogeneity test and hypothesis test. Based on data from result of research used to obtain is 3.88 and at 5% significance level of 1.991. Because t-test > t-table so the results of this research indicate that there were significant difference toward leraning outcome between experimental class use 5E Learning Model and control class use direct learning model on human nervous system concept. Keyword: 5E Learning Model, Learning Outcomes.